Strand symmetry and nonrandom DNA trimer arrangement in yeast Saccharomyces cerevisiae chromosomes - Huyen, Phan Thi; Luong, Nguyen Duc (Academia Journal of Biology, 2013)
According to the Chargaff’s second parity rule, the eukaryotic chromosomes have been reported to be strand symmetric. However, how the nucleotides are arranged in the chromosome and why the chromosomes possess this strand symmetric property have not been known. We found in Saccharomyces cerevisiae that although the frequencies of trimers and those of their respective reverse complements in the whole single stranded sequence of chromosome were almost equal, they were remarkably different in the local regions of chromosome. Results of investigation on trimer arrangement in the intergenic sequences as well as in the sense and antisense sequences of chromosome showed that the frequencies of trimers and those of their respective reverse complements in the intergenic sequences of chromosome were approximately the same, and that the trimer arrangement in the sense and antisense sequences of chromosome shaped the codon usage. The chromosomal strand symmetry is the consequence of the equal distribution of trimers and their respective reverse complements.